Inovasi Strategi Pemasaran Berbasis Digital untuk Meningkatkan Daya Saing Perusahaan - Grace Yulianti; Sigit Pramono; Seger Santoso (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Digital transformation has encouraged companies to adopt innovation in digital-based marketing strategies to increase competitiveness in an increasingly competitive and dynamic business era. This study examines in depth the role of innovation in digital marketing strategies, including the use of search engine optimization (SEO), social media marketing, interactive content, and the use of data analytics in marketing decision making. The method used is a literature review approach by reviewing various previous studies to identify key elements of an effective and adaptive digital marketing strategy. The results of the study indicate that the application of innovative digital technology can expand market reach, increase operational efficiency, strengthen customer engagement, and create a more personal and valuable customer experience. These findings underline the importance of continuous innovation, technology adaptation, and rapid response to digital market trends. Thus, this study provides practical guidance for companies in designing relevant, competitive, and future-oriented digital marketing strategies.